Technology and religious tourism : emerging trends, cases and futuristic perspectives - Tyagi, Pankaj Kumar; Singh, Pramendra; Sharma, Neha; Bhatt, Vaibhav (Entrepreneurship and technology in tourism and hospitality, 2025)
Religious tourism is a phenomenon dating back thousands of years, that engages people from all walks of life, from across the entire globe. It is an inseparable part of many human lives. Pilgrimage and spiritual tourism are often considered an essential part of the religion itself. The contemporary environment, especially owing to the large-scale use of technology, has greatly changed the pattern and process of religious tourism. Be it pilgrim management, ticket generation, the safety and security of pilgrims and premises, facilitating movement, maintaining the religious centre, controlling access, educating the pilgrims, providing religious souvenirs - are all quickly and efficiently managed by technology. Technology has made it possible to smoothen the visit to religious tourism destinations, make it accessible to everyone, and even enhance the religious experience. Technology and Religious Tourism: Emerging Trends, Cases and Futuristic Perspectives covers the application, adaptability and implications of technology in religious tourism. Authors from different countries and religious backgrounds cover the theoretical aspects of the relation of religious tourism with technology, while highlighting global cases, contemporary trends and potential future trends. This book will be suitable for students, the research community, and academics who wish to study new dimensions of religious tourism, with respect to its adoption of modern technology.